2020
DOI: 10.1084/jem.20190742
|View full text |Cite
|
Sign up to set email alerts
|

Blimp-1 is essential for allergen-induced asthma and Th2 cell development in the lung

Abstract: A Th2 immune response is central to allergic airway inflammation, which afflicts millions worldwide. However, the mechanisms that augment GATA3 expression in an antigen-primed developing Th2 cell are not well understood. Here, we describe an unexpected role for Blimp-1, a transcriptional repressor that constrains autoimmunity, as an upstream promoter of GATA3 expression that is critical for Th2 cell development in the lung to inhaled but not systemically delivered allergens but is dispensable for TFH function … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 77 publications
0
36
0
Order By: Relevance
“…Similarly, the role of Blimp-1 in the immune system is highly context dependent and tissue specific. For example, it was recently shown that Blimp-1 is an unexpected positive regulator of Th2 responses in the lung, facilitated through an IL-10/STAT3 axis ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the role of Blimp-1 in the immune system is highly context dependent and tissue specific. For example, it was recently shown that Blimp-1 is an unexpected positive regulator of Th2 responses in the lung, facilitated through an IL-10/STAT3 axis ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, Uwadiae et al 100 discovered that the administration of anti‐ICOS ligand antibody specifically disrupted T FH cell responses, accompanied by reduced lung inflammation and airway hyper‐responsiveness in a mouse asthma model induced by HDM. In a similar model, He et al 101 reported that the deletion of Blimp‐1 upregulated Bcl‐6 expression in CD4 + T cells, leading to the suppression of Gata3 expression and T H 2 cell differentiation. Their results suggest distinct mechanisms underpinning T FH and T H 2 cell differentiation in response to allergens and Blimp‐1 as a rheostat oppositely determining T FH vs T H 2 fate commitment in the murine model of allergic asthma.…”
Section: Tfh and Tfr Cells In Allergic Diseasesmentioning
confidence: 95%
“…As a result of their efforts, they not only confirmed GATA3, Stat6, Batf, PPARγ, and IRF4 as key transcription factors that are involved in Th2 cell differentiation and activation but also revealed Bhlhe40, Bcl11b, and Xbp1 as transcription factors that are involved in Th2 cell activation. While more factors that are involved in regulating Th1/Th2 differentiation and functions are still being discovered, including the p53 family protein p73, which affects Th1 cell differentiation 63 , and Blimp-1, which regulates GATA3 expression and thus Th2 cell differentiation 64 , the combination of novel genome-level technologies such as CRISPR knockout with high-throughput sequencing will hopefully reveal more non-lineage-related transcription factors in modulating CD4 T cell differentiation.…”
Section: New Roles For Known Transcription Factors In Regulating the mentioning
confidence: 99%